"Enjoying the Four Olds!": Oral histories from a "cultural desert" - Mittler, Barbara (The journal of transcultural studies, 2013)
The traumatic experience of having one’s home broken into, precious objects—books, records, paintings, and musical instruments—destroyed and looted, has been described in many a memoir or fictional account from the Cultural Revolution. However, these narratives, which have become well known as emblematic examples of the Cultural Revolution experience, often leave out the flipside of these intrusions: the question of what happened to the objects after they had been taken?Starting out from the experiences related in a set of interviews that were conducted with representatives from different generations and social groups, this paper offers an alternative reading of this and similar campaigns: one that emphasizes assiduous reading and listening, and learning from the cultural objects that were confiscated from some so as to be enjoyed by others. The paper argues that the experience of “smashing (and enjoying) the Four Olds” was extremely transcultural: contrary to common notions that see the Chinese Cultural Revolution as a period of political and cultural iconoclasm as well as of isolationism, and consequently a “cultural desert,” the paper provides extensive evidence of a vibrant and transculturally informed experience of cultural consumption. This involved both China’s traditional and foreign cultural products which, even if officially banned, were unofficially available, especially during the “smashing” campaign and similar campaigns that followed.